A fluorogenic cyclic peptide for imaging and quantification of drug-induced apoptosis - Barth, Nicole D.; Subiros-Funosas, Ramon; Mendive-Tapia, Lorena; Duffin, Rodger; Shields, Mario A.; Cartwright, Jennifer A.; Henriques, Sónia Troeira; Sot, Jesus; Goñi, Felix M.; Lavilla, Rodolfo; Marwick, John A.; Vermeren, Sonja; et al. (Nature communications, 2020)
Programmed cell death or apoptosis is a central biological process that is dysregulated in many diseases, including inflammatory conditions and cancer. The detection and quantification of apoptotic cells in vivo is hampered by the need for fixatives or washing steps for non-fluorogenic reagents, and by the low levels of free calcium in diseased tissues that restrict the use of annexins. In this manuscript, we report the rational design of a highly stable fluorogenic peptide (termed Apo-15 ) that selectively stains apoptotic cells in vitro and in vivo in a calcium-independent manner and under wash-free conditions. Furthermore, using a combination of chemical and biophysical methods, we identify phosphatidylserine as a molecular target of Apo-15 . We demonstrate that Apo-15 can be used for the quantification and imaging of drug-induced apoptosis in preclinical mouse models, thus creating opportunities for assessing the in vivo efficacy of anti-inflammatory and anti-cancer therapeutics. Programmed cell death or apoptosis is an essential biological process that is impaired in some diseases and can be used to assess the effectiveness of drugs. Here the authors design Apo-15 as a fluorogenic peptide for the detection and real-time imaging of apoptotic cells.